Liberating Discipline Pedagogy in Indonesian Character Education - Fandy Ahmad (Al-Munawwarah: Journal of Islamic Education, 2025)
Discipline in Indonesian education is often addressed through external control rather than internal growth. This study seeks to address this issue by exploring how Stephen R. Covey’s 7 Habits model can be adapted to reconceptualize discipline as a liberating process that fosters independence, moral responsibility, and collective well-being. The research aims to bridge the global discipline model with the character education paradigm in Indonesia. Using a qualitative library research design with purposive sampling of global and national literature (2016–2025), the data were analyzed through content analysis to identify thematic patterns connecting the 7 Habits, discipline, and local religious-cultural traditions. The findings show that the 7 Habits implement discipline through self-regulation, prioritization, collaboration, empathy, synergy, and holistic renewal, with positive yet context-dependent impacts on students’ discipline, leadership, and socio-emotional growth. In the Indonesian context, integration with values such as ikhlas (sincerity), mujahadah al-nafs (self-discipline), and ta’dhim al-mu’allim (respect for teachers) strengthens discipline as a value-based practice within school culture. This study concludes that aligning global disciplinary principles with local wisdom produces a contextual approach to character education and provides conceptual contributions to the development of value-based discipline models as well as practical implications for curriculum design and educational policy.